2016
DOI: 10.1186/s12974-016-0543-5
|View full text |Cite
|
Sign up to set email alerts
|

6-Mercaptopurine attenuates tumor necrosis factor-α production in microglia through Nur77-mediated transrepression and PI3K/Akt/mTOR signaling-mediated translational regulation

Abstract: BackgroundThe pathogenesis of several neurodegenerative diseases often involves the microglial activation and associated inflammatory processes. Activated microglia release pro-inflammatory factors that may be neurotoxic. 6-Mercaptopurine (6-MP) is a well-established immunosuppressive drug. Common understanding of their immunosuppressive properties is largely limited to peripheral immune cells. However, the effect of 6-MP in the central nervous system, especially in microglia in the context of neuroinflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 81 publications
2
38
0
Order By: Relevance
“…In this study, in which once again LPS was used to induce inflammatory responses in cultured primary microglia or murine BV-2 microglial cells, it was reported that 6-MP was able to adverse TNF-α mRNA translation through prevention of LPS activated PI3K/Akt/mTOR signaling cascades. These results corroborated the idea that the modulation of PI3K/Akt/mTOR signaling might contribute to the downregulation of microglia mediated inflammation, suggesting its possible therapeutic application in neuroinflammation related neurodegenerative disorders [72].…”
Section: Pi3k Role In Neuroinflammationsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, in which once again LPS was used to induce inflammatory responses in cultured primary microglia or murine BV-2 microglial cells, it was reported that 6-MP was able to adverse TNF-α mRNA translation through prevention of LPS activated PI3K/Akt/mTOR signaling cascades. These results corroborated the idea that the modulation of PI3K/Akt/mTOR signaling might contribute to the downregulation of microglia mediated inflammation, suggesting its possible therapeutic application in neuroinflammation related neurodegenerative disorders [72].…”
Section: Pi3k Role In Neuroinflammationsupporting
confidence: 84%
“…In addition, it was demonstrated that well established immunosuppressive drug 6 mercaptopurine (6-MP) was able to downregulate microglial inflammatory responses by modulating microglial TNF-α production, suggesting the possible mechanism of this modulation [72]. In this study, in which once again LPS was used to induce inflammatory responses in cultured primary microglia or murine BV-2 microglial cells, it was reported that 6-MP was able to adverse TNF-α mRNA translation through prevention of LPS activated PI3K/Akt/mTOR signaling cascades.…”
Section: Pi3k Role In Neuroinflammationmentioning
confidence: 99%
“…LPS induces inflammation by activating microglia and produces various proinflammatory cytokines (Smith et al, 2012). Based on these properties, microglial cells treated with LPS are widely used as an in vitro cell model of neuroinflammation, as well as a tool for the evaluation of potential antineuroinflammatory compounds (Gupta and Kaur, 2016;Huang et al, 2016;Pfluger et al, 2016). Thus, this cell model was used in the present study to evaluate the antineuroinflammatory effect of FCPR03.…”
Section: Discussionmentioning
confidence: 99%
“…Nur77, a transcription factor of the nuclear receptor, plays important roles in neuroinflammation, cell proliferation, differentiation, apoptosis, metabolism and development 2 7 8 9 10 . In humans, three family members have been identified: nerve growth factor IB (also known as Nur77, NR4A1, or TR3), Nuclear receptor related 1 (also known as Nurr1, or NR4A2), and neuron-derived orphan receptor 1 (Nor-1, NR4A3).…”
mentioning
confidence: 99%